LITERATUR RIVIEW: PERUBAHAN MATERI GENETIK - Kinanti, Aulian Andin; Khairani , Miftahul; Syahfitri , Dini Indah; Lubis , Fazil Mawla; Sinurat , Yulianti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Human creation must be understood through stages of growth and development, where in the process of growth and development humans experience interactions or relationships that influence each other between basic abilities or innate abilities and acquired abilities, namely through learning and influence from the environment. This research was conducted by analyzing 10 journals. The keywords used were "changes in genetic material", "genetics", and "influence of genetic factors". The articles selected were articles that met the inclusion criteria: maximum journal publication deadline of 14 years (2010-2024). Of the 10 articles submitted Seven of them were used in this literature review shows that there is a significant relationship regarding changes in genetic material.